PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN SISA LEBIH PEMBIAYAAN ANGGARAN BELANJA MODAL PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2013-2015 - Ribka Cahya Wulandari, 14.05.52.0116; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2018)
This study aims to test and analyze the effect of the Fund Local, General Allocation Fund, Specific Allocation Fund, Financing Budget Surplus Area of Capital Expenditure in the Ditricts/Cities in Central Java Province in 2013-2015.The sample in this study covers all cities/districts in Central Java province during the year 2013-2015 as many as 105 data. The analysis tools used are multiple linear regression test.Based on the research that has been done, found that Local Own Revenue, General Allocation Fund,Specific Allocation Fund, and Financing Budget Surplus Area has a significant positive effect on Capital Expenditure.Keywords: Fund Local Own Revenue, General Allocation Fund, Specific Allocation Fund, Financing Budget Surplus Area and Capital Expenditure